Search for Neutrinos from Annihilating Dark Matter in the Direction of the Galactic Center with the 40-String IceCube Neutrino Observatory - collaboration, TI; Abbasi, R; Abdou, Y; Ackermann, M; Adams, J; Aguilar, J; Ahlers, M; Altmann, D; Andeen, K; Auffenberg, J; Bai, X; Baker, M; et al. (2012)
A search for muon neutrinos from dark matter annihilations in the Galactic Center region has been performed with the 40-string configuration of the IceCube Neutrino Observatory using data collected in 367 days of live-time starting in April 2008. The observed fluxes were consistent with the atmospheric background expectations. Upper limits on the self-annihilation cross-section are obtained for dark matter particle masses ranging from 100 GeV to 10 TeV. In the case of decaying dark matter, lower limits on the lifetime have been determined for masses between 200 GeV and 20 TeV.